THE USE OF DIGITAL TECHNOLOGY IN TEACHING FIQH TO STUDENTS AT MTS AL BADAR BILALANG - Ali, An.Muhammad; Jamilah Amin, Sitti; Thahir, Abdullah; Herda, Herda; Marhani, Marhani (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2025)
Islamic religious education in the digital era faces the challenge of remaining relevant for digital native generations, particularly in the subject of Fiqh, which is procedural and practical in nature, at the madrasah tsanawiyah level. Although previous studies have explored the integration of digital technology at the madrasah aliyah or ibtidaiyah levels, there remains a gap in contextual analysis of technology utilization and the challenges faced by teachers at Madrasah Tsanawiyah (MTs), especially in regions such as Parepare. This study aims to identify the types of digital technology used by Fiqh teachers, describe the processes of its utilization in teaching, and analyze the obstacles encountered at MTs Al Badar Bilalang Parepare. The research employs a descriptive phenomenological qualitative approach, with data collected through participatory observation, in-depth interviews with teachers and students, and document analysis, including lesson plans (RPP) and teaching materials. Data analysis follows the Miles and Huberman model, supported by NVivo software for thematic coding and triangulation. The findings reveal that Fiqh teachers utilize digital technology comprehensively, encompassing hardware (WiFi, laptops, projectors, Smart TVs) and software (PowerPoint, YouTube, e-books, digital journals), integrated systematically from the planning stage to implementation, tailored to practical worship materials to enhance visualization and interactivity.